2011
DOI: 10.1371/journal.pone.0020920
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MTDH Sensitizes Endometrial Cancer Cells to Cell Death Induction by Death Receptor Ligand TRAIL and HDAC Inhibitor LBH589 Co-Treatment

Abstract: Understanding the molecular underpinnings of chemoresistance is vital to design therapies to restore chemosensitivity. In particular, metadherin (MTDH) has been demonstrated to have a critical role in chemoresistance. Over-expression of MTDH correlates with poor clinical outcome in breast cancer, neuroblastoma, hepatocellular carcinoma and prostate cancer. MTDH is also highly expressed in advanced endometrial cancers, a disease for which new therapies are urgently needed. In this present study, we focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 37 publications
6
38
0
Order By: Relevance
“…This finding is consistent with a previous study that showed knockdown of AEG-1 could decrease the colony formation in SiHa cells. 36 Furthermore, that AEG-1 knockdown led to reduced NF-kB expression (Fig. 4C) is also consistent with our previous finding that NF-κB played important roles in more quiescent cancer stem-like cells than in the bulk cells.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a previous study that showed knockdown of AEG-1 could decrease the colony formation in SiHa cells. 36 Furthermore, that AEG-1 knockdown led to reduced NF-kB expression (Fig. 4C) is also consistent with our previous finding that NF-κB played important roles in more quiescent cancer stem-like cells than in the bulk cells.…”
Section: Discussionsupporting
confidence: 92%
“…Third, MTDH was shown to co-localize with the RNAinduced silencing complex (RISC) component staphylococcal nuclease domain-containing-1 (SND1) (20,21). Finally, we recently reported that depletion of MTDH alters expression of several MTDH downstream genes, and MTDH is mainly cytoplasmic in the endometrial cancer cell lines used in this study (14).…”
Section: Mtdh Is Primarily Cytoplasmic In Endometrial and Ovarian Cancermentioning
confidence: 62%
“…Colony Formation-Stable MTDH or control shRNA Hec50 cells were established as reported previously (14). Cells were treated with mitomycin C (MMC) for 24 h and then cultured in normal medium for 2 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have indicated that AEG-1/MTDH contributes to several steps in human oncogenesis, including cancer cell progression, invasion, metastasis, and chemoresistance (39). It is reported that overexpression of AEG-1/ MTDH promotes activation of the pro-survival pathway of PI3K/AKT via up-regulation of PIP3 (40). These facts suggest that miR-375 is a direct regulator of the YWHAZ/14-3-3ζ and AEG-1/MTDH oncogenes, and that this phenomenon is important to HNSCC and MSSCC oncogenesis.…”
Section: Discussionmentioning
confidence: 99%